Kompetensi Pendidik di Pesantren Salafiyah Lukmanul Hakim Medan - Rambe, Nazila Fujianti; Harahap, Hasti Ananda; Hasibuan, Agus Salim; Hutagalung, Rahmad Rizki (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The competence of educators is one of the major factors in determining the quality of education in an institution. Quality educator personnel not only master the subject matter but also possess pedagogical competencies that can support the learning process. This is listed in Law no. 14 Year 2005 on Teachers and Lecturers that teachers are professional educators who have the primary task of educating, teaching, guiding, directing, training, assessing, and evaluating learners. The study aimed to analyze the pedagogical competencies of an educator in carrying out his/her duties and responsibilities in schools. The research method used was a descriptive qualitative approach through interviews with a teacher. The results of the study show that the diverse characteristics of students demand teachers to be able to understand them where it is necessary in designing suitable lesson strategies. Teachers adapt methods, media, and forms of assessment to suit students diverse learning styles. Challenges faced by teachers in the learning process such as character differences, social media, and time constraints can be overcome with a professional approach. Within the learning process lie strategies that are not only in delivering the material, but also in shaping students character and social skills.